Investigation in fuel cells using 'hydro-genius teach' - Isa, Muzamir (2004)
The aim of this report is to deliver information's about the features of fuel cells. Along with it, this report gives details about activities of renewable energy. It covers analysis of theories and some experiments done using a set of tool called Hydro Genius Teach. The experiments are about advantages of fuel cells compared to other methods that have been used to produce electrical energy from the processes of renewable energy. Furthermore, methods on how fuel cells operate are also given. The main objective of this project was to analyse current usage of renewable energy in the world. The main focus is to do analysis on features of fuel cells as one of ways in renewable energy.